Synchronous delivery of oxygen and photosensitizer for alleviation of hypoxia tumor microenvironment and dramatically enhanced photodynamic therapy. (1st January 2018) - Guo, Xiaomeng; Qu, Jiaxin; Zhu, Chunqi; Li, Wei; Luo, Lihua; Yang, Jie; Yin, Xiaoyi; Li, Qingpo; Du, Yongzhong; Chen, Dawei; Qiu, Yunqing; Lou, Yan; et al.
Abstract: Photosensitizer, proper laser irradiation, and oxygen are essential components for effective photodynamic therapy (PDT) in clinical cancer therapy. However, native hypoxic tumoral microenvironment is a major barrier hindering photodynamic reactions in vivo . Thus, we have prepared biocompatible liposomes by loading complexes of oxygen-carrier (hemoglobin, Hb) and photosensitizer (indocyanine green, ICG) for enhanced PDT against hypoxic tumor. Ideal oxygen donor Hb, which is an oxygen-carried protein in red blood cells, makes such liposome which provide stable oxygen supply. ICG, as a photosensitizer, could transfer energy from lasers to oxygen to generate cytotoxic reactive oxygen species (ROS) for treatment. The liposomes loading ICG and Hb (LIH) exhibited efficient tumor homing upon intravenous injection. As revealed by T 2 -weighted magnetic resonance imaging and immunohistochemical analysis, the intratumoral hypoxia was greatly alleviated, and the level of hypoxia inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) in tumor was obviously down-regulated. A weak PDT efficiency was found in cells incubated in simulated hypoxia condition in vitro, while PDT effect was dramatically enhanced in LIH treated hypoxia cells under near-infrared (NIR) laser, which was mainly attributed to massive generation of ROS with sufficient oxygen supply. ROS trigger oxidative damage of tumors and induce complete suppression of tumor growth and 100% survival rate of mice, which were also in good health condition. Our work highlights a liposome-based nanomedicine that could effectively deliver oxygen to tumor and alleviate tumor hypoxia state, inducing greatly improved efficacy compared to conventional cancer PDT and demonstrates the promise of modulating unfavorable tumor microenvironment with nanotechnology to overcome limitations of cancer therapies.